Analisis pengelolaan dana desa pada masa pandemi Covid-19 di Kabupaten Bengkulu Selatan - Titi Darmi; Iqbal Mifktahul Mujtahid; Bella Aurel Ichzani; Bella Dian Nusantara (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
This research was inspired by the government policies that shifted the priority of village fund management during the Covid-19 pandemic to the previous Direct Cash Assistance (BLT) program, in general village funds were prioritized for development activities. This research aims to find out and analyze how village funds are managed during the Covid-19 pandemic in Padang Berangin Village and Pagar Dewa Village in 2019 and 2020. The method used was a skin-descriptive approach. The data source was conducted by direct interview to the relevant informant and equipped with related documents. Informant determination was selected by using Purpoisive Sampling. The data collection techniques were conducted with observation, interview and documentation. Technical analysis of the data used was reduction, presentation of data, and withdrawal of conclusions. The results of this research showed that the management of village funds in Padang Berangin Village and Pagar Dewa Village has been done well. Planning is carried out by developing with the community to set the priority of budget activities. Budgeting is carried out in accordance with village APBD by involving the community in its work activities. Organizing is carried out by determining the implementation team of the selected activities and determined based on the Decree (SK) by the village head. Reporting is done in a transparent manner to the public. The solution offered by the researcher is that the community should be more active in participating in village fund management activities as well as installing information media in affordable places as a form of transparency to the community.